Detection of Hepatitis E Antibodies in Kazakhstan: A Pilot Study - Cainelli, Francesca; Hortelano, Gonzalo; Negmetzhanov, B.; Ibrayeva, A.; Kaliaskarova, Kulpash; Bulanin, Denis; Vento, Sandro (University of Pittsburgh, University Library System, 2018)
Introduction. Hepatitis E virus exposure is associated with sporadic cases of acute hepatitis and outbreaks in many countries worldwide. It is particularly dangerous for pregnant women, in whom the mortality rate is high. There are no previously published data reporting circulation of this virus in Kazakhstan. Methods. We tested blood samples for IgG anti-hepatitis E virus antibodies in 199 Kazakh participants; of these 119 were workers at the EXPO 2017 building site in Astana, 35 were volunteers who got tested at the Astana City Hall on the World Hepatitis Day 2017, and 45 were volunteers who presented for screening at the Hepatogastroenterology Outpatient Clinic of the Republican Diagnostic Center, University Medical Center. Results. 11 (5.5%) individuals were positive for IgG anti-HEV antibodies, with a higher seroprevalence in males (7; 6.8%) vs females (4; 4.5%). The highest number of positive samples was in the 32-46 years age group. Conclusions. This pilot study suggests that Hepatitis E virus has been circulating in Kazakhstan. Studies are needed to determine whether it continues to be present, which viral genotypes are involved and what are the best methodologies for preventing its spread.
http://cajgh.pitt.edu/ojs/index.php/cajgh/article/view/324
Keywords: Hepatitis E; anti-HEV antibodies; Kazakhstan; Research Subject Categories::MEDICINE